How to make an efficient gas-phase heterogeneous CO2 hydrogenation photocatalyst. Issue 9 (11th August 2020) - Yan, Tingjiang; Li, Na; Wang, Linlin; Liu, Qin; Jelle, Abdinoor; Wang, Lu; Xu, Yangfan; Liang, Yan; Dai, Ying; Huang, Baibiao; You, Jinmao; Ozin, Geoffrey A.
Abstract : rh/c-In2 O3− x (OH) y with precisely adjustable fractions of rhombohedral and cubic phases were synthesized and enabled boosting photocatalytic performance toward CO2 hydrogenation. Abstract : Tailoring the performance of a photocatalyst by design is challenge in the field of renewable synthetic fuels. Herein, polymorphic heterostructures comprised of two indium oxide based photocatalysts, with distinct structures yet continuously adjustable fractions of the same composition, enable optimization of the activity and selectivity of CO2 hydrogenation to CO and CH3 OH. The strategy rests on the cubic (c-) to rhombohedral (rh-) indium oxide hydroxide In2 O3− x (OH) y phase transition, in which the fraction of the cubic phase that nucleates and grows within the rhombohedral phase is under precise structural and compositional control. Interfaces so-formed between cubic and rhombohedral polymorphs with distinct electronic band structures as well as separate locations of electron trapping oxygen vacancies and hole trapping hydroxyl defects in individual In2 O3− x (OH) y components, enable charge generation, separation and lifetimes of photogenerated electron–hole pairs to be finely tuned. This facilitates command over H2 and CO2 surface chemical reactions that are responsible for the activity and selectivity towards products CO and CH3 OH. The control over the performance metrics of a CO2 hydrogenation photocatalyst provided by tuneable rh/c-In2 O3− x (OH) y polymorphic heterostructures, affords promising opportunities for the future development of renewable synthetic fuels.